Maternal Separation Induces Sex-Specific Differences in Sensitivity to Traumatic Stress - Knox, Dayan; Stout-Oswald, Stephanie A.; Tan, Melissa; George, Sophie A.; Liberzon, Israel (Frontiers in Behavioral Neuroscience, 2021)
Post traumatic stress disorder (PTSD) is a debilitating psychiatric disorder with a high economic burden. Two risk factors for increasing the chances of developing PTSD are sex (being female) and early life stress. These risk factors suggest that early life stress-induced changes and sex differences in emotional circuits and neuroendocrinological systems lead to susceptibility to traumatic stress. Exploring mechanisms via which stress leads to specific effects can be accomplished in animal models, but reliable animal models that allow for an examination of how early life stress interacts with sex to increase susceptibility to traumatic stress is lacking. To address this, we examined the effects of early life stress (using the maternal separation (MS) model) and late adolescence/early adult traumatic stress (using the single prolonged stress (SPS) model) on startle reactivity, anxiety-like behavior in the open field (OF), and basal corticosterone levels in male and female rats. Female rats exposed to MS and SPS (MS/SPS) showed enhanced startle reactivity relative to MS/control female rats. Enhanced startle reactivity was not observed in MS/SPS male rats. Instead, non-maternally separated male rats that were exposed to SPS showed enhanced startle reactivity relative to controls. Female rats had enhanced locomotor activity in the OF and higher basal corticosterone levels in comparison to males, but measures in the OF and basal corticosterone were not affected by MS or SPS. Overall the results suggest that the combined MS and SPS models can be used to explore how changes in maternal care during infancy lead to sex differences in sensitivity to the effects of traumatic stress as adolescents and adults.